Pengaruh Permainan Sobas Terhadap Keterampilan Passing Bola Basket - Nanda Bagus Tri Cahya Saputra; Saifuddin, Hasan; Cahyani, Olivia Dwi (Jurnal Porkes, 2026)
Poor basketball passing skills among tenth-grade students at SMAN 4 Bojonegoro are a major problem, likely caused by a monotonous learning approach that lacks contextual variation. This study aims to examine the effect of applying the modified SOBAS game (integrating gobak sodor with basketball techniques) on improving passing skills. The research method used a quantitative approach with a one-group pretest-posttest design. A total of 36 students were selected as subjects through purposive sampling. Chest pass, bounce pass, and overhead pass skills were measured using the Johnson basketball test instrument before and after the intervention. The treatment was the SOBAS game. Data analysis results showed a very significant increase in all three types of passing. The average chest pass score rose from 17.72 to 39.61; bounce pass from 16.03 to 38.83; and overhead pass from 16.72 to 39.31. The Paired Sample t-Test statistical test produced a significance value of 0.000 (<0.05) for all variables, confirming a significant difference between the pretest and posttest results. The conclusion indicates that the SOBAS game is an effective and innovative learning model for improving basketball passing skills in high school students, as it is able to create dynamic, contextual learning situations and encourage the integrated development of technical skills.